Influence of the Distribution of Pits on the Friction and Wear Performance of Textured Rolling Bearings under Starved Lubrication - Yazhe Chen; Risheng Long; Zhihao Jin; Chen Zhao; Ming Wang (Lubricants, 2023)
Most of the published documents on the friction and wear properties of textured contact surfaces with partially distributed units (e.g., dots, grooves) are focused on sliding tribo-pairs or journal bearings. To study the friction and wear performance of rolling bearings with different distributions of pits, several patterns were introduced: OS-1/4 (Outside, 1/4 of raceway), OS-1/2 (Outside, 1/2 of raceway), OS-3/4 (Outside, 3/4 of raceway), IS-1/4 (Inside, 1/4 of raceway), IS-1/2 (Inside, 1/2 of raceway), IS-3/4 (Inside, 3/4 of raceway), TS (Two sides, 2/3 of raceway), FT (fully textured) and SR (Smooth reference), with two circumferential interval angles (CFIAs, 1.5° and 2.0°). The dimensions of the pits are the same in all patterns (diameter of 300 μm and depth of 15 μm), which were only prepared on the raceways of the shaft washers of 81107 bearings (nylon cages) using the laser marking method. All bearings were tested under 4000 N, 250 RPM and starved lubrication using a vertical universal wear test rig. Their mass losses and worn raceways were measured and observed. Their surface equivalent stresses were also analyzed and compared. The obtained results show that the influence of different distributions of pits on the tribological properties of rolling bearings is significant. The friction-reducing and anti-wear performance of TS is acceptable, whether the CFIA is 1.5° or 2.0°. A fully textured pattern cannot provide the best tribological properties and its behavior even becomes worse when the CFIA is 2.0°. In this work, when the CFIA is 1.5°, the friction-reducing and anti-wear performance of OS-1/4 is the best among all patterns. Using a smooth reference as a benchmark for comparison, its friction-reducing and anti-wear performance can be enhanced by 60.46% and 16.05%, respectively. The results of this work will be an important reference for the optimal design of the “washers-cage-rollers” contact system for rolling bearings.